Responsible Research and Innovation (RRI) through technology: implications for international market orientation in agribusiness cooperatives - Sánchez Hernández, María Isabel; Castilla Polo, Francisca (REVESCO. Revista de Estudios Cooperativos, 2025)
Incorporating new technologies into cooperatives is pivotal for both Responsible Research and Innovation (RRI) in these organizations and their internationalization. RRI has particular prominence in the European research policy landscape, offering a sustainability framework aimed at harmonizing economic, socio-cultural, and environmental dimensions within current innovation paradigms. Despite the growing importance of RRI, there is still a dearth of literature on its application within the cooperative sector. Focusing on Spain’s foremost agribusiness cooperatives, this study seeks to establish a comprehensive measurement scale for RRI with a specific emphasis on technological integration, which is then used to evaluate the correlation between RRI and these enterprises’ international market orientation. To that end, we apply Structural Equation Modelling to data sourced from a questionnaire administered to 60 managers selected from the 100 most reputable cooperatives in the country. Our empirical findings show that agribusiness cooperatives actively promote technology adoption among members, facilitate technology development processes, and embrace open innovation strategies to exhibit heightened international market orientation. These insights should not only drive agro-industry practitioners to prioritize technology adoption but should also encourage policymakers to accelerate the technological advancement of the economy.